Younger Onset Dementia: A Review of the Literature to Inform Service Development. (December 2016) - Sansoni, Janet; Duncan, Cathy; Grootemaat, Pamela; Capell, Jacquelin; Samsa, Peter; Westera, Anita
This literature review focused on the experience, care, and service requirements of people with younger onset dementia. Systematic searches of 10 relevant bibliographic databases and a rigorous examination of the literature from nonacademic sources were undertaken. Searches identified 304 articles assessed for relevance and level of evidence, of which 74% were academic literature. The review identified the need for (1) more timely and accurate diagnosis and increased support immediately following diagnosis; (2) more individually tailored services addressing life cycle issues; (3) examination of the service needs of those living alone; (4) more systematic evaluation of services and programs; (5) further examination of service utilization, costs of illness, and cost effectiveness; and (6) current Australian clinical surveys to estimate prevalence, incidence, and survival rates. Although previous research has identified important service issues, there is a need for further studies with stronger research designs and consideration of the control of potentially confounding factors.